IMPLEMENTASI PERSYARATAN UNESCO GLOBAL GEOPARK (UGG) PADA GEOSITE AIR TERJUN SIPISO-PISO KABUPATEN KARO PROVINSI SUMATERA UTARA - Harmoko S., Samuel (Akademi Pariwisata Darma Agung, 2025)
UNESCO Global Geopark is ageological parklocate dinanarea that has acollection ofgeological heritage that has Passthe UNESCO Global Geopark criteria. The emphasis of this study is on two things: (1) the current state of the Sipiso-Piso Waterfall Geosite, and (2) the interdisciplinary implementation of the UNESCO Global Geopark criteria on Sipiso-Piso Waterfall Geosite. Thisstudy employed a descriptive qualitative research method with case studies that involve field observations, in-depth interviews with stakeholders, and document analysis. Geodiversity analysis of existing conditions through contouring of geosite factors indicates that Sipiso-Piso Waterfall Geosite has geodiversity geological and ecological potential, but also among the geortsites have many environmental management challenges and conservation. Some of the problems discovered: infrastructure that has yet to be improved, public awareness that has yet to be increased, and waste management that is not yet optimal. This study concludes that the application of UNESCO Global Geopark requirements on the Geosite of Sipiso-Piso Waterfall has been made with a good degree ofsuccess,and the extensive and integrated existing efforts, however, it still need sindependence and led to the intiation of the Standard expected.The source softhe additions include enhanced capabilities and infrastructure, representcooperation and partnerships, as well as expanded education and public outreach.